Baicalein improves behavioral dysfunction induced by Alzheimer’s disease in rats - Zhou L; Tan S; Shan YL; Wang YG; Cai W; Huang XH; Liao XY; Li HY; Zhang L; Zhang BJ; Lu ZQ (Neuropsychiatric Disease and Treatment)
Li Zhou, Sha Tan, Yi-long Shan, Yu-ge Wang, Wei Cai, Xue-hong Huang, Xi-yuan Liao, Hai-yan Li, Lei Zhang, Bing-jun Zhang, Zheng-qi Lu Department of Neurology, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China Background: Alzheimer’s disease (AD) is considered to be a neurodegenerative disorder that is characterized by increased oxidative stress. Medicinal plants, with their antioxidant properties, have been used to cure several human diseases. The aim of the current study was to explore the protective and therapeutic effect of baicalein on AD-induced rats. Materials and methods: Swiss Wistar rats were used in the study. The rats were divided into five groups. Group I: normal control group treated with water; Group II: disease control treated with AlCl3 to induce the mimicking AD for 4 successive weeks (SW); Group III: normal control group treated with baicalein (5 mg/kg) for 2 SW followed by combination of baicalein and AlCl3 for 4 SW; Group IV: normal control group treated with baicalein (10 mg/kg) for 2 SW followed by combination of baicalein and AlCl3 for 4 SW; Group V: normal control group treated with rivastigmine (0.3 mg/kg) for 2 SW followed by combination of rivastigmine and AlCl3 for 4 SW. Moreover, the therapeutic groups are as follows: Group VI: AD disease control treated with AlCl3 for 4 SW and serving as the therapeutic positive group; Group VII: AD disease control + baicalein (5 mg/kg) for 12 SW; Group VIII: AD disease control + baicalein (10 mg/kg) for 12 SW; Group IX: AD disease control + rivastigmine (0.3 mg/kg) for 12 SW. Behavioral test, T-maze, and rotarod test were also performed before and after the treatment. At the end of the experimental study, all the rats were sacrificed and their brains were removed and divided into two portions. The first portion was homogenated for estimating the level of acetylcholinesterase (AchE) and acetylcholine (Ach). Another portion was used for histopathological evaluation. Results: The current investigation showed that baicalein significantly reduced the duration of revolving on the rotarod, cage activity, and T-maze activity in a dose-dependent manner compared with the AD control group rats. It also altered the AchE and Ach levels in the brain homogenates. The histopathology study also provides strength to the protective effect of baicalein. Conclusion: The current study showed that baicalein significantly (P<0.05) improved the biochemical and histopathological condition of AD in rats. Keywords: baicalein, Alzheimer’s disease, acetylcholinesterase, acetylcholine